Penerapan Batuk Efektif pada Ketidakefektifan Bersihan Jalan Nifas Penderita Asma Bronkhial - Suprayitna, Marthilda; Asrianti, Mugi; Arifin, Zainal (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2022)
Background: Asthma is a non-communicable disease characterized by recurrentattacks of shortness of breath and wheezing. Asthma begins with asthmaallergens that will cause antigen and antibody reactions. This reaction releasesvasoactive substances that cause increased sputum secretion and airwayobstruction. Effective cough technique is one of the efficient non-pharmacologicaltreatments because it can be done easily and effectively to expel phlegm inasthmatics. Objective: The purpose of this case study is to describe nursing careby applying effective coughing to expel phlegm in bronchial asthma patients.Methods: This study is a descriptive study in Orong Dalam Village, Lingar Districtin June-July 2021. The samples in this study were two adult bronchial asthmasufferers using interview, observation and physical examination methods.Results: The results of this study indicate that the application of coughingtechniques is effective. proven to be able to help clients who do not have theability to cough to expel phlegm effectively and efficiently. Before the procedure,the client cannot expel phlegm effectively and efficiently, and after the action ofgiving effective coughing techniques for 6 times, the client's effective coughingability increases and can perform effective coughing techniques independently.Conclusion: The application of an effective cough technique is very effective inremoving phlegm in patients with bronchial asthma. Suggestion: For furtherresearchers, they can work together with local health workers to conductcounseling and counseling activities to increase knowledge and provideinformation, especially about bronchial asthma and effective coughing techniques.Keywords: bronchial asthma, phlegm, effective cough technique, ineffectiveairway clearance, nursing care